Using system dynamics to evaluate renewable electricity development in Malaysia. Issue 1 (28th January 2014) - Ahmad, Salman; bin Mat Tahar, Razman
Abstract : Purpose: – The purpose of this paper is to provide an assessment of Malaysia's renewable capacity target. Malaysia relies heavily on fossil fuels for electricity generation. To diversify the fuel-mix, a technology-specific target has been set by the government in 2010. Considering the complexity in generation expansion, there is a dire need for an assessment model that can evaluate policy in a feedback fashion. The study also aims to expand policy evaluation literature in electricity domain by taking a dynamic systems approach. Design/methodology/approach: – System dynamics modelling and simulation approach is used in this study. The model variables, selected from literature, are constituted into casual loop diagram. Later, a stock and flow diagram is developed by integrating planning, construction, operation, and decision making sub-models. The dynamic interactions between the sub-sectors are analysed based on the short-, medium- and long-term policy targets. Findings: – Annual capacity constructions fail to achieve short-, medium- and long-term targets. However, the difference in operational capacity and medium- and long-term target are small. In terms of technology, solar photovoltaic (PV) attains the highest level of capacity followed by biomass. Research limitations/implications: – While financial calculations are crucial for capacity expansion decisions, currently they are not being modelled; this study primarily focuses on system delays and exogenous components only. Practical implications: – A useful model that offers regulators and investors insights on system characteristics and policy targets simultaneously. Originality/value: – This paper provides a model for evaluating policy for renewable capacity expansion development in a dynamic context, for Malaysia.